Gas Phase Oxidation of Carbon Monoxide by Sulfur Dioxide Radical Cation: Reaction Dynamics and Kinetic Trend With the Temperature - Catone, Daniele; Satta, Mauro; Cartoni, Antonella; Castrovilli, Mattea C.; Bolognesi, Paola; Turchini, Stefano; Avaldi, Lorenzo (Frontiers in Chemistry, 2019)
Gas phase ion chemistry has fundamental and applicative purposes since it allows the study of the chemical processes in a solvent free environment and represents models for reactions occurring in the space at low and high temperatures. In this work the ion-molecule reaction of sulfur dioxide ion SO2.+ with carbon monoxide CO is investigated in a joint experimental and theoretical study. The reaction is a fast and exothermic chemical oxidation of CO into more stable CO2 by a metal free species, as SO2.+, excited into ro-vibrational levels of the electronic ground state by synchrotron radiation. The results show that the reaction is hampered by the enhancement of internal energy of sulfur dioxide ion and the only ionic product is SO.+. The theoretical approach of variational transition state theory (VTST) based on density functional electronic structure calculations, shows an interesting and peculiar reaction dynamics of the interacting system along the reaction path. Two energy minima corresponding to [SO2–CO].+ and [OS–OCO].+ complexes are identified. These minima are separated by an intersystem crossing barrier which couples the bent 3B2 state of CO2 with C2v symmetry and the 1A1 state with linear D∞h symmetry. The spin and charge reorganization along the minimum energy path (MEP) are analyzed and eventually the charge and spin remain allocated to the SO.+ moiety and the stable CO2 molecule is easily produced. There is no bottleneck that slows down the reaction and the values of the rate coefficient k at different temperatures are calculated with capture theory. A value of 2.95 × 10−10 cm3s−1molecule−1 is obtained at 300 K in agreement with the literature experimental measurement of 3.00 × 10−10 ± 20% cm3s−1molecule−1, and a negative trend with temperature is predicted consistently with the experimental observations.